Untersuchungen zur Altersabhängigkeit der traumatisch induzierten ossären Umbaureaktion im Skelettszintigramm - Spitz, J.; Lauer, I.; Tittel, K. (Nuklearmedizin - NuclearMedicine, 1991)
Two independent groups of patients were studied by bone scintigraphy to demonstrate age-dependent changes in the appearance time of fractures: 83 patients with 123 fractures of the spine showed neither by multiple regression analysis nor by separation into two subgroups (younger and older than 55 years) a clinical significant difference by scintimetric evaluation. A second group of 162 polytraumated patients demonstrated no age dependence of the rate of additional bone lesions shown by scintigraphy. Instead a clear dependence on the site of the lesion and the time after trauma was found: fractures of the shafts of long bones and fractures of the pelvis and spine showed up significantly later than fractures in the neighbourhood of the distal joints. 12-14 days after a trauma all fractures may be detected with a high accuracy independently from the fracture site (except for fractures of the skull which did not show up at all in most cases). Thus, the differences in the appearing time of fractures are not age- but site-dependent.